MANAJEMEN PERTUNJUKAN SANGGAR SENI BUDAYA BINA MUSIK DAN VOKALIA “SRIKANDI” DI KOTA SAWAHLUNTO - Violyn Sagita Khintani; Ediwar Ediwar; Sriyanto Sriyanto (Bajang Institute, 2023)
This study examines the management and form of performance of the Cultural Arts Studio Bina Musik and Vokalia Srikandi, Sawahlunto City. The studio was born from the interest of the members of the vocal group consisting of Darmawoman members in the Sawahlunto City environment for Javanese Gamelan art in the Bina Laras Sawahlunto Studio, where the majority of the players consist of men, both young and old. The uniqueness of the Srikandi City Music and Vokalia Art and Culture Studio in Sawahlunto City itself lies in the form of songs that the studio produces, not only songs originating from Javanese traditions, but also Minang, Papuan, Shalawat songs, and songs composed by the Music Development Cultural Arts Studio. and Vokalia Srikandi City of Sawahlunto. The purpose of this study was to describe the management and forms of performance of the Srikandi City Music and Vokalia Cultural Arts Studio in Sawahlunto. This study uses qualitative research methods with data collection techniques by observation, documentation, and field interviews to obtain research results according to context that are descriptive in nature. The results of this study explain the management and form of performances of the Srikandi Music and Vokalia Cultural Arts Studio in Sawahlunto City.